The integrin binding peptide, atn-161, as a novel therapy for SARS-CoV-2 infection (2020)
Many efforts to design and screen therapeutics for the current severe acute respiratory syndrome coronavirus (SARS-CoV-2) pandemic have focused on inhibiting viral host cell entry by disrupting ACE2 binding with the SARS-CoV-2 spike protein. This work focuses on the potential to inhibit SARS-CoV-2 entry through a hypothesized α5β1 integrin-based mechanism, and indicates that inhibiting the spike protein interaction with α5β1 integrin (+/- ACE2), and the interaction between α5β1 integrin and ACE2 using a novel molecule ATN-161 represents a promising approach to treat COVID-19.